2014
DOI: 10.1016/j.meatsci.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quercetin dietary supplementation on meat oxidation processes and texture of fattening lambs

Abstract: 26Thirty two lambs were fed a total mixed ration (TMR) formulated either with palm 27 oil (CTRL; 34 g palm oil kg -1 TMR) or whole flaxseed (+FS, 85 g flaxseed kg -1 TMR) 28 alone or enriched with quercetin (+QCT, 34 g palm oil plus 2 g quercetin kg -1 TMR; 29 +FS+QCT, 85 g flaxseed plus 2 g quercetin kg -1 TMR). Dietary flaxseed did not affect, 30 in a significant manner, the lipid peroxidation of meat samples. Quercetin treatment 31 reduced oxysterols content (P < 0.05) after 7 days of refrigerated storage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
3
11
1
4
Order By: Relevance
“…In further studies, supplementation of the lamb diet with 250-1000 mg α-tocopherol kg −1 feed extended the shelf life of meat kept under MAP by up to 4 days due to its reduction of lipid and haem pigment oxidation, although the resultant sensory traits were not assessed. Moreover, vitamin E was seen to have no effect on microbial inhibition on meat (Álvarez et al, 2008;Lauzurica et al, 2005;Ripoll et al, 2011) In recent years, several alternative dietary strategies based on plant phenolic antioxidants have been successfully checked for improving lamb meat preservation (Andrés et al, 2014(Andrés et al, , 2013Jerónimo et al, 2012;Luciano et al, 2009;Rivas-Cañedo et al, 2013;Simitzis, Ilias-Dimopoulos, Charismiadou, Biniari, & Deligeorgis, 2013;Simitzis et al, 2008), and, in particular, by using rosemary and/or its derivatives (Bañón et al, 2012;Morán, Rodríguez-Calleja, et al, 2012;Morán et al, 2013;Nieto, Díaz, Bañón, & Garrido, 2010;Ortuño, Serrano, Jordán, & Bañón, 2014;. Carnosic acid and, in particular, carnosol, the main active diterpenes in rosemary, can be deposited in lamb muscle at sufficient levels to have antimicrobial and antioxidant effects on meat (Jordán, Castillo, Bañón, Martínez-Conesa, & Sotomayor, 2014;Moñino, Martínez, Sotomayor, Lafuente, & Jordán, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In further studies, supplementation of the lamb diet with 250-1000 mg α-tocopherol kg −1 feed extended the shelf life of meat kept under MAP by up to 4 days due to its reduction of lipid and haem pigment oxidation, although the resultant sensory traits were not assessed. Moreover, vitamin E was seen to have no effect on microbial inhibition on meat (Álvarez et al, 2008;Lauzurica et al, 2005;Ripoll et al, 2011) In recent years, several alternative dietary strategies based on plant phenolic antioxidants have been successfully checked for improving lamb meat preservation (Andrés et al, 2014(Andrés et al, , 2013Jerónimo et al, 2012;Luciano et al, 2009;Rivas-Cañedo et al, 2013;Simitzis, Ilias-Dimopoulos, Charismiadou, Biniari, & Deligeorgis, 2013;Simitzis et al, 2008), and, in particular, by using rosemary and/or its derivatives (Bañón et al, 2012;Morán, Rodríguez-Calleja, et al, 2012;Morán et al, 2013;Nieto, Díaz, Bañón, & Garrido, 2010;Ortuño, Serrano, Jordán, & Bañón, 2014;. Carnosic acid and, in particular, carnosol, the main active diterpenes in rosemary, can be deposited in lamb muscle at sufficient levels to have antimicrobial and antioxidant effects on meat (Jordán, Castillo, Bañón, Martínez-Conesa, & Sotomayor, 2014;Moñino, Martínez, Sotomayor, Lafuente, & Jordán, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that phenolic compounds have the capacity to act as powerful antioxidants by scavenging free radicals and terminating oxidative reactions. This statement has been corroborated by several authors who included various flavonoid groups in lamb diets (Andrés et al, 2014a), showing satisfactory results with regard to meat peroxidation stability. Winemaking by-products have been associated with effective antioxidant activity in beef (Ahn et al, 2002), lamb meat and sheep plasma , so they could be an alternative to synthetic antioxidant additives.…”
Section: Introductionsupporting
confidence: 57%
“…En este sentido, ha sido señalado que el efecto de los polifenoles sobre el perfil lipídico de la carne es más evidente cuando se emplean grasas muy insaturadas en las raciones. Así, Andrés et al (2014a) al incluir el flavonol quercetina observó un incremento en el nivel de RA de la carne de cordero únicamente cuando la dieta fue suplementada con aceite de linaza. pH El pH de la carne está relacionado con los procesos bioquímicos de transformación del músculo en carne.…”
Section: Perfil De áCidos Grasosunclassified
See 1 more Smart Citation
“…The COPs, also called oxysterols, were determined, according to the method described by Andrés et al . (). Further details have been included in Appendix S1.…”
Section: Methodsmentioning
confidence: 97%